Reproductive autonomy associated with the use of contraceptive methods among reproductive aged women - Ana Luiza Vilela Borges; Ana Cleide da Silva Dias; Carolina Cavalcante da Silva Ale (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To assess the sociodemographic aspects associated with reproductive autonomy among urban women, with special regard to the relationship with the use of contraceptive methods. Method: Cross-sectional study with 1252 women, conducted between April and June 2021, using the Brazilian version of the Reproductive Autonomy Scale. Data were analyzed using multiple linear regression. Results: Mean scores for the subscales were 2.5 (SD=0.3) (Decision-making), 3.8 (SD=0.3) (Absence of Coercion) and 3.6 (SD=0.4) (Communication). Compared to women who reported no use of contraceptive methods, women using barrier or behavioral methods and those using LARC had higher level of reproductive autonomy on all dimensions of the Scale (p<0.001). Other aspects associated with reproductive autonomy were education, race/ethnicity, religion, socioeconomic status and cohabitation living with a partner, depending on each subscale. Conclusion: The type of contraceptive method used was statistically associated with reproductive autonomy in all subscales.